The Effect of Reading Wheel Media on the Beginning Reading Skills of First-Grade Elementary School Students - Salma Widyanik; Oktiana Handini; Ani Restuningsih (Madako Elementary School, 2026)
Beginning reading difficulties remain a concern in elementary education, particularly among first-grade students who struggle to recognize letters, distinguish speech sounds, and read simple words fluently. Preliminary observations at SDN 1 Gagaksipat indicated limited use of varied instructional media in beginning reading instruction. This study examined the effect of Reading Wheel media on first-grade students’ beginning reading skills. A quantitative pre-experimental study using a one-group pretest-posttest design involved 27 students. Data were collected using a validated and reliable reading test and analyzed through a paired-samples t-test and N-Gain analysis. The mean score increased from 67.85 on the pretest to 85.37 on the posttest, representing a 17.52-point gain. The paired-samples t-test indicated a statistically significant improvement (t = 15.552, p < .05), while the N-Gain score of 0.5453 indicated moderate improvement. These findings suggest that Reading Wheel media has potential to improve beginning reading performance by engaging students through visual and kinesthetic learning activities. The findings provide a practical alternative for diversifying beginning reading instruction, although further research using controlled experimental designs and broader samples is needed to establish its effectiveness and generalizability.